Investigation of optical and radiation shielding characteristics of Gd2O3-doped tellurium zinc borate glass via melt-quenching method - Nazrin, S. N.; Thakur, S.; Doroody, C.; Zaman, H.; Nashruddin, S. N. A. M.; Faznny, Mohd Fudzi (Elsevier Ltd., 2025)
The melt-quenching approach was used to produce Gd2O3-doped tellurium zinc borate glass system with composition {[(TeO2)0.7(B2O3)0.3]0.7(ZnO)0.3}1− x(Gd2O3)x where x = 0.01, 0.02, 0.03, 0.04 as well as 0.05 M fraction and assess its optical and radiation shielding characteristics. Phy-X/PSD software was used to calculate parameters such as mass attenuation coefficient (MAC), linear attenuation coefficient (LAC), half value layer (HVL), tenth value layer (TVL), and mean free path (MFP) in order to evaluate the effectiveness of radiation shielding. Glass containing 0.05 M fraction of Gd2O3 exhibited the greatest shielding efficacy, surpassing conventional concretes such as chromite and serpentine. The refractive index dropped from 2.518 to 2.352 while the direct and indirect optical band gaps increased from 3.239 to 3.519 eV and from 2.587 to 3.172 eV, respectively. The amorphous nature of the glass was validated by XRD, while TeO3, TeO4, BO3, and BO4 vibrational groups were identified by infrared spectra demonstrating the potential of the prepared glass for optical and radiation shielding applications.